Antinuclear Antibodies Elevated in Cutaneous Leishmaniasis Patients: Diagnostic Implications - Noor Talal Ali; Shahad Saad Daham; Dema kamal Mustafa (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Leishmaniasis is a widespread parasitic disease transmitted by sandfly bites, posing significant public health challenges in developing countries, with cutaneous leishmaniasis being particularly prevalent in Iraq. Specific Background: While clinical diagnosis remains standard, immunological markers including specific antibodies (IgM, IgG) have been explored for cutaneous leishmaniasis detection, yet the diagnostic potential of antinuclear antibodies (ANA) remains underutilized. Knowledge Gap: The role of ANA as an immunological biomarker for cutaneous leishmaniasis diagnosis in Tikrit has not been comprehensively investigated. Aims: This serological study examined ANA levels and specific antibody responses in 60 clinically diagnosed cutaneous leishmaniasis patients at Tikrit Teaching Hospital from October 2023 to January 2024. Results: Males showed higher infection rates (53.33%) than females (46.66%); the 1-5 year age group exhibited the highest prevalence (31.66%); dry ulcers predominated (78.33%, p<0.01); 75% of patients demonstrated IgM antibodies, 5% showed IgG, and 20% tested negative; significantly, ANA levels were elevated in both male and female patients compared to controls (p<0.05). Novelty: This study establishes ANA as a valuable supplementary immunological marker for cutaneous leishmaniasis diagnosis in the Tikrit region. Implications: The findings suggest that ANA testing could enhance diagnostic accuracy and understanding of autoimmune responses in cutaneous leishmaniasis, potentially improving patient management strategies.Keywords : Cutaneous Leishmaniasis, Antinuclear Antibodies, Immunological Markers, Serological Diagnosis, Tikrit EpidemiologyHighlight : Dry ulcers predominated at 78.33%, significantly higher than wet ulcers at 21.66%. Rural residents showed 71.66% infection rate compared to 43.33% in urban areas. Seventy-five percent of patients exhibited IgM antibodies indicating acute infection phase.